The new digital age : transforming nations, businesses, and our lives - Schmidt, Eric, 1955 April 27-; Cohen, Jared, 1981- (2014)
In collaboration, two leading global thinkers from in technology and foreign affairs from Google give readers their widely anticipated, transformational vision of the future: a world where everyone is connected, a world full of challenges and benefits that are ours to meet and to harness. With their combined knowledge and experiences, the authors are uniquely positioned to take on some of the toughest questions about our future: Who will be more powerful in the future, the citizen or the state? Will technology make terrorism easier or harder to carry out? What is the relationship between privacy and security, and how much will we have to give up to be part of the new digital age? In this they combine observation and insight to outline the promise and peril awaiting us in the coming decades. This is a forward-thinking account of where our world is headed and what this means for people, states and businesses. With the confidence and clarity of visionaries, the authors illustrate just how much we have to look forward to, and beware of, as the greatest information and technology revolution in human history continues to evolve. On individual, community and state levels, across every geographical and socioeconomic spectrum, they reveal the dramatic developments both good and bad, that will transform both our everyday lives and our understanding of self and society, as technology advances and our virtual identities become more and more fundamentally real. As their nuanced vision of the near future unfolds, an urban professional takes his driverless car to work, attends meetings via hologram and dispenses housekeeping robots by voice; a Congolese fisherwoman uses her smart phone to monitor market demand and coordinate sales (saving on costly refrigeration and preventing overfishing); the potential arises for "virtual statehood" and "Internet asylum" to liberate political dissidents and oppressed minorities, but also for tech-savvy autocracies (and perhaps democracies) to exploit their citizens' mobile devices for ever more ubiquitous surveillance. Along the way, we meet a cadre of international figures, including Julian Assange, who explain their own visions of our technology-saturated future. This book is an analysis of how our hyper-connected world will soon look.
Introduction -- Our Future Selves -- The Future of Identity, Citizenship and Reporting -- The Future of States -- The Future of Revolution -- The Future of Terrorism -- The Future of Conflict, Combat and Intervention -- The Future of Reconstruction -- Conclusion -- Afterword.
"With a new afterword"--Cover.
Includes bibliographical references (pages 285-337) and index.
Keywords: Digital media -- Social aspects -- Forecasting; Digital media -- Political aspects -- Forecasting; Digital electronics -- Social aspects -- Forecasting; Digital electronics -- Political aspects -- Forecasting; Information technology -- Social aspects -- Forecasting; Information technology -- Political aspects -- Forecasting; Computers and civilization -- Forecasting; Technology and civilization -- Forecasting